Winkler Prins Geschiedenis der Nederlanden. Onder red. van: J.A. Bornewasser, R.C. van Caenegem e.a. Auteurs: A. d'Haenens, H.P.H. Jansen e.a (Elsevier, 1977)
Bibl., reg. 1. Van de prehistorie tot de Bourgondische periode